TEACHING WRITING DESCRIPTIVE TEXTS TO THE EIGHTH YEAR STUDENTS: “PUT YOURSELF IN THE PICTURE” ACTIVITY - Permatasari, Krisdian Eka (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
Writing is considered as a complicated and difficult skill to be mastered by the students. Several difficulties are found in learning of descriptive writing. Dealing with the case, the research questions are proposed as follows: (1) How is “Put Yourself in the Picture” activity implemented by the teacher in teaching descriptive texts? and (2) How are the results of the students in writing descriptive texts in the aspects of grammar, vocabulary, content and organization through the implementation of “Put Yourself in the Picture” activity? This research is qualitative design in which the researcher acted as the observer to collect information as the evidences in the writing class to find the teacher’s and students’ activities in implementing “Put Yourself in the Picture” activity in the three stages of teaching learning process in writing descriptive texts. The results of the research showed that the teacher and the students implemented “Put Yourself in the Picture” activity in some of the these activities, as follows: (1) introducing the essay topic; (2) listing the words or phrases relating to the topic; (3) Making sentences based on the listed ideas; (4) identifying the generic structures and language features of descriptive text; (5) Writing the descriptive text; (6) Making groups and giving feedbacks of the writing’ results; (7) Editing and re writing the final drafts. Besides, the students’ learning writing progresses are described into five categories. They are (1) very good student’s score category; (2) good student’s score category; (3) fair student’s score category; (4) poor student’s score category; and (5) very poor student’ score category. These criteria are based on the students’ writing results analyzed in the aspects of grammar, vocabulary, content, and organization.